Stroke phases and coordination index around maximal lactate steady state in swimming - Pelarigo, J. G.; Denadai, B. S.; Fernandes, B. D.; Santiago, D. R. P.; César, T. E. A. S.; Barbosa, L. F.; Greco, C. C. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: Alberty et al. (2009) verified decrease of nonpropulsive phases and maintenance increase of the propulsive phases during exhaustive tests (95, 100 and 110% of maximal 400-m swimspeed test). There is no data referring to the stroke strategies to maintain the speed during long-distance swims, which are found during some swim training sessions and long-distance events. The aim of this study was to analyze changes in stroke parameters (i.e., stroke length - SL and stroke rate - SR) and arm coordination (i.e., propulsive and nonpropulsive phases and IdC) when swimming at and above (102.5%) maximal lactate steady state (MLSS). METHODS: Twelve endurance swimmers (21 ± 8 yr.) performed in different days: 1) 200 and 400-m all-out tests to determine critical speed (CS), and; 2) two to four 30- min sub-maximal continuous tests at imposed swim pace, to determine the MLSS. Video analysis was used to determine the SR, SL, stroke phases and IdC. The IdC was determined using the lag times between the propulsive phases of each arm (Chollet et al., 2000). Blood lactate and stroke technique variables were analyzed at 10th and 30th minute of each imposed speed test. RESULTS: There was significant difference among MLSS (1.22± 0.05 m/s), 102.5% MLSS (1.25 ± 0.04 m/s) and CS (1.30 ± 0.08 m/s). SR and SL was maintained during the test swum at MLSS and have modified at 102.5% MLSS (SR - 30.98 ± 3.44 and 32.26 ± 3.56 cycles/min and SL - 2.47 ± 0.22 and 2.38 ± 0.24 m/cycle). All stroke phases maintained during the test swum at MLSS. However, the propulsive phase B (pull) increased at 102.5% MLSS (21.7 ± 3.4% and 22.9 ± 3.9%). There was no significant effect of exercise intensity and time on IdC. CONCLUSIONS The changes in stroke parameters (i.e., reduction in SL and increase in SR) and arm coordination (i.e., increase in propulsive phase B) of well trained swimmers during long distance imposed speed tests performed at heavy intensity domain (ie., below CS), occurs only at condition of non-metabolic equilibrium. These changes are important to increase the duration over which the propulsive force acted per distance unit as the force capacity was reduced.